Oxidative Difunctionalization of Alkenyl MIDA Boronates: A Versatile Platform for Halogenated and Trifluoromethylated α‐Boryl Ketones. (22nd July 2016) - Lv, Wen‐Xin; Zeng, Yao‐Fu; Li, Qingjiang; Chen, Yunyun; Tan, Dong‐Hang; Yang, Ling; Wang, Honggen
Abstract: The synthesis of halogenated and trifluoromethylated α‐boryl ketones via a one‐pot oxidative difunctionalization of alkenyl MIDA boronates is reported. These novel densely functionalized organoborons bearing synthetically and functionally valuable carbonyl, halogen/CF3 and boronate moieties within the same molecule are synthetically challenging for the chemist, but have great synthetic potential, as demonstrated by their applications in a straightforward synthesis of borylated furans. The generality of this reaction was extensively investigated. This reaction is attractive since the starting materials, alkenyl MIDA boronates, are easily accessible.